Characterization of Avian Pathogenic Escherichia coli (APEC) Associated With Turkey Cellulitis in Iowa - Aline Luisa de Oliveira; Darby M. Newman; Yuko Sato; Andrew Noel; Britney Rauk; Lisa K. Nolan; Nicolle L. Barbieri; Catherine M. Logue (Frontiers in Veterinary Science, 2020)
Turkey cellulitis, also known as clostridial dermatitis is a significant cause of morbidity, mortality, and carcass condemnation at slaughter resulting in considerable losses for turkey producers. Here, we assessed the potential role of Avian Pathogenic Escherichia coli (APEC) in a cellulitis outbreak on a turkey farm in Iowa. Birds from one farm with a history of cellulitis and one farm with no history of disease (for comparison) were followed from the age of 10 weeks (before the outbreak) to 18 weeks (just prior to slaughter). E. coli recovered from the litter, from skin lesions of birds with cellulitis, and from systemic lesions of birds submitted for necropsy, were assessed. A total of 333 isolates were analyzed and screened for virulence-associated genes, antimicrobial resistance genes including heavy metal resistance, adhesins, invasins, and protectins, iron acquisition systems and their phylogenetic group through multiplex PCR. In addition, PCR was used to serogroup the isolates, and pulsed field gel electrophoresis (PFGE) was used to analyze a subset of strains from the farm environment (litter) and birds at 17 and 18 weeks of age when the cellulitis infection appeared to peak. Overall, E. coli isolates recovered from cellulitis lesions and systemic infection were identified as APEC, while a lower prevalence of E. coli recovered from the litter met the criteria of APEC-like. Direct comparison of E. coli isolates from the litter, lesions, and systemic strains using PFGE failed to find identical clones across all three sources reflecting the diversity of strains present in the poultry environment causing disease. This study highlights the role of APEC in turkey cellulitis and should not be overlooked as a significant contributor to the disease in turkeys.